Relationship Between Short Birth Length And Stunting Incidence In Toddlers - Elisa Goretti Sinaga; Ega Ersya Urnia; Diah Ulfa Hidayati; Lidia Lushinta; Harmi Ulbandriyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: The length of a baby's birth can describe linear growth during pregnancy. If a baby is born with a short body length, it indicates a disorder during pregnancy which usually indicates a state of malnutrition suffered by the mother. Short birth length is a risk factor for stunting Objectives: The purpose of this study was to determine the relationship between short birth length and the incidence of stunting Methods: The type of research used was correlation analytic with a cross-sectional design. The research location was at the Bengkuring Health Center, Samarinda City, East Kalimantan Province. The number of samples was 30 people with inclusion criteria, toddlers aged 2-5 years who experienced stunting with a history of mothers giving birth at term. The sampling technique used was Purposive Sampling. Data collection used KIA books, Microtoise to measure toddler height, scales to measure toddler weight, KMS sheets to see the baby's birth length, and nutritional reports at the Health Center. Data analysis techniques used univariate and bivariate analysis using the chi-square test Results: Most of the children's birth weight is normal (2500-4000 gr) totaling 23 people (76.7%), then the birth length of the children is mostly short (<48 cm) totaling 20 people (66.7%). All toddlers in this study were classified as stunted, namely 30 people (100%). Bivariate analysis using the chi-square test with a ρ-value = 0.000 Conclusions: There is a relationship between short birth length and the incidence of stunting